lncRNAs: the unexpected link between protein synthesis and cancer adaptation - Mila Gugnoni; Manoj Kumar Kashyap; Kishore K. Wary; Alessia Ciarrocchi (Molecular Cancer)
Abstract Cancer progression relies on the ability of cells to adapt to challenging environments overcoming stresses and growth constraints. Such adaptation is a multifactorial process that depends on the rapid reorganization of many basic cellular mechanisms. Protein synthesis is often dysregulated in cancer, and translational reprogramming is emerging as a driving force of cancer adaptive plasticity. Long non-coding RNAs (lncRNAs) represent the main product of genome transcription. They outnumber mRNAs by an order of magnitude and their expression is regulated in an extremely specific manner depending on context, space and time. This heterogeneity is functional and allows lncRNAs to act as context-specific, fine-tuning controllers of gene expression. Multiple recent evidence underlines how, besides their consolidated role in transcription, lncRNAs are major players in translation control. Their capacity to establish multiple and highly dynamic interactions with proteins and other transcripts makes these molecules able to play a central role across all phases of protein synthesis. Even if through a myriad of different mechanisms, the action of these transcripts is dual. On one hand, by modulating the overall translation speed, lncRNAs participate in the process of metabolic adaptation of cancer cells under stress conditions. On the other hand, by prioritizing the synthesis of specific transcripts they help cancer cells to maintain high levels of essential oncogenes. In this review, we aim to discuss the most relevant evidence regarding the involvement of lncRNAs in translation regulation and to discuss how this specific function may affect cancer plasticity and resistance to stress. We also expect to provide one of the first collective perspectives on the way these transcripts modulate gene expression beyond transcription.